2019
DOI: 10.1136/bjsports-2018-100164
|View full text |Cite
|
Sign up to set email alerts
|

Concussed athletes walk slower than non-concussed athletes during cognitive-motor dual-task assessments but not during single-task assessments 2 months after sports concussion: a systematic review and meta-analysis using individual participant data

Abstract: ObjectivesTo determine whether individuals who sustained a sports concussion would exhibit persistent impairments in gait and quiet standing compared to non-injured controls during a dual-task assessment .DesignSystematic review and meta-analysis using individual participant data (IPD).Data sourcesThe search strategy was applied across seven electronic bibliographic and grey literature databases: MEDLINE, EMBASE, CINAHL, SportDISCUS, PsycINFO, PsycARTICLES and Web of Science, from database inception until June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 101 publications
(216 reference statements)
4
46
0
Order By: Relevance
“…12 Previous research has demonstrated that BIs and repetitive subconcussive head impacts in other populations (e.g., contact sport athletes, military personnel, people experiencing homelessness) are often associated with alterations in cognitive-motor performance. [12][13][14][15][16] Given the chronic and repetitive nature of IPV, it is likely that alterations in cognitive-motor function may also be present in survivors of IPV-related BI. Thus, the purpose of this study was to characterize cognitive-motor function in women who have experienced IPV and examine the extent to which it was related to clinical measures of executive function.…”
Section: Introductionmentioning
confidence: 99%
“…12 Previous research has demonstrated that BIs and repetitive subconcussive head impacts in other populations (e.g., contact sport athletes, military personnel, people experiencing homelessness) are often associated with alterations in cognitive-motor performance. [12][13][14][15][16] Given the chronic and repetitive nature of IPV, it is likely that alterations in cognitive-motor function may also be present in survivors of IPV-related BI. Thus, the purpose of this study was to characterize cognitive-motor function in women who have experienced IPV and examine the extent to which it was related to clinical measures of executive function.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these impairments were not highlighted by traditional clinical assessments, but were captured using inertial sensor technology. These findings are part of a growing body of evidence demonstrating that deficits in sensorimotor function may exist beyond clinical recovery post-concussion, 6,7,39 contributing to an increased risk of future injury. 4 As such, clinicians and rehabilitation specialists should introduce targeted balance training interventions into the return to play process to accelerate sensorimotor control recovery and mitigate the risk of future injury.…”
Section: Perspecit Vementioning
confidence: 81%
“…5 These concerns are beginning to be substantiated, with research demonstrating that sensorimotor control deficits post-clinical recovery from concussion may be more pronounced during dynamic balance 6 and dual-task situations. 7 Furthermore, research has demonstrated that laboratory-based kinetic and kinematic evaluation during gait and balance tasks can detect deficits in those with a history of concussion, when compared to healthy controls. 8,9 As such, the objective and quantifiable evaluation of movement control during dynamic tasks may provide a means to sufficiently challenge the sensorimotor system in individuals who have sustained a concussion, uncovering persistent sub-clinical performance deficits which may increase an individual's risk of injury.…”
mentioning
confidence: 99%
“…However, gait speed only reflect global gait performance and provides limited understanding of impairments seen in different pathologies [13], which is where a more comprehensive approach may add value. Similarly, gait characteristics, other than gait speed, may be useful for non-invasive discrimination between pathologies [40][41][42], with potential for gait to become a diagnostic tool for mTBI. Appropriate gait characteristics selection for mTBI studies would benefit from a more systematic and informed approach, which is where our developed gait model could add value to future studies.…”
Section: Future Directionsmentioning
confidence: 99%